Psycholinguistic Basis of the Formation of Early Artificial Bilingualism - Dehkanova Dilnoza Tashpulatovna (International Journal on Integrated Education, 2021)
the article discusses the problems of creating early artificial bilingualism (the methodological equivalent of the term: early learning of a foreign language) from the point of view of psycholinguistics and the theory of speech activity. The basic principles and approaches to the organization of the process of formation of early bilingualism outside the natural language environment are presented. The authors are based on the works of famous psycholinguists. The leading scientific positions in this case are the acoustic nature of language and the emotional nature of speech. These assumptions allow us to form approaches to early learning of a non-native language that do not contradict the process of natural acquisition of a non-native language. The presence of universal and nationally specific signs of speech is taken into account.